Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(\frac{45}{7}-\frac{\frac{3}{4}x-2}{\frac{7}{20}}\right).\frac{14}{5}=10\)
\(\frac{45}{7}-\frac{\frac{3}{4}x-2}{\frac{7}{20}}=\frac{25}{7}\)
\(\frac{\frac{3}{4}x-2}{\frac{7}{20}}=\frac{20}{7}\)
\(\frac{3}{4}x-2=1\)
\(\frac{3}{4}x=3\)
\(x=4\)
Vậy x=4
\(\frac{3}{x-5}=-\frac{4}{x+2}\)
\(\Leftrightarrow3\left(x+2\right)=-4\left(x-5\right)\)
\(\Leftrightarrow3x+6=-4x+20\)
\(\Leftrightarrow7x=14\)
\(\Leftrightarrow x=2\)
\(\frac{x}{-2}=-\frac{8}{x}\)
\(\Leftrightarrow x^2=16\)
\(\Leftrightarrow x=\pm4\)
\(-\frac{2}{x}=\frac{y}{3}\)
\(\Leftrightarrow xy=-6\)
\(\Leftrightarrow x;y\inƯ\left(-6\right)=\left\{\pm1;\pm2;\pm3;\pm6\right\}\)
Xét bảng
x | 1 | -1 | 2 | -2 | 3 | -3 | 6 | -1 |
y | -6 | 6 | -3 | 3 | -2 | 2 | -1 | 6 |
Vậy.................
\(\frac{2x-9}{240}=\frac{39}{80}\)
\(\Leftrightarrow2x-9=\frac{240.39}{80}\)
\(\Leftrightarrow2x-9=117\)
\(\Leftrightarrow2x=126\)
\(\Leftrightarrow x=63\)
\(\frac{-5}{x}=\frac{-y}{8}=\frac{18}{72}\)
\(\Leftrightarrow\frac{-5}{x}=\frac{-y}{8}=\frac{1}{4}\)
\(\Leftrightarrow\orbr{\begin{cases}-\frac{5}{x}=\frac{1}{4}\\-\frac{y}{8}=\frac{1}{4}\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=-5.4:1\\-y=8.1:4\end{cases}\Leftrightarrow\orbr{\begin{cases}x=-20\\-y=2\end{cases}\Leftrightarrow}\orbr{\begin{cases}x=-20\\y=-2\end{cases}}}\)
vậy x=-20 và y=-2
a) \(x-\frac{10}{3}=\frac{7}{15}\cdot\frac{3}{5}\) b) \(x+\frac{3}{22}=\frac{27}{121}\cdot\frac{11}{9}\)
\(\Leftrightarrow x-\frac{10}{3}=\frac{7}{25}\) \(\Leftrightarrow x+\frac{3}{22}=\frac{3}{11}\)
\(\Rightarrow x=\frac{7}{25}+\frac{10}{3}\) \(\Rightarrow x=\frac{3}{11}-\frac{3}{22}\)
\(x=\frac{271}{75}\) \(x=\frac{3}{22}\)
c) \(\frac{8}{23}.\frac{46}{24}-x=\frac{1}{3}\) d) \(1-x=\frac{49}{65}.\frac{5}{7}\)
\(\Leftrightarrow\frac{2}{3}-x=\frac{1}{3}\) \(\Leftrightarrow1-x=\frac{7}{13}\)
\(\Rightarrow x=\frac{2}{3}-\frac{1}{3}\) \(\Rightarrow x=1-\frac{7}{13}\)
\(x=\frac{1}{3}\) \(x=\frac{6}{13}\)
b) \(\frac{3}{x-5}=\frac{-4}{x+2}\)
=> 3.(x + 2) = (x - 5). (-4)
= 3x + 6 = -4x + 20
= 3x - 4x = 26
=> -x = 26
=> x = -26
c) \(\frac{x}{-2}=\frac{-8}{x}\)
=> x.x = -2 . (-8)
=> x2 = 16
=> x = 4
t i c k nha!!! 645646677778879078452352543546456457567564546567